La pedagogía musical para el desarrollo de las habilidades sensoriales auditivas de los niños del Centro de Desarrollo Infantil “Estrellitas del Futuro" del cantón Guaranda, provincia Bolívar, durante el periodo 2019-2020 - Gavilánez Borja, Karen Lizvette (2020)
The purpose of this research is to substantiate the educational importance of Musical Pedagogy for the development of sensory abilities in children from 2 to 3 years of age in the child development center "Estrellitas del Futuro" in the canton of Guaranda, Bolívar province. Design pedagogical strategies based on Musical Pedagogy to be applied with children from 2 to 3 years old for the development of sensory skills that allow them to improve their integral development from an early age. Identify the achievements made in the development of sensory skills from the musical pedagogy applied to children in the child development center "Estrellitas del Futuro", to measure their degree of perception through the pedagogy of the musical, since the child always he learns by listening to music and develops his auditory, visual and kinesthetic abilities, which allows the infant to be a person with active skills and abilities. Music is the source of knowledge, everything in the world has rhythm, even language is a source of melody, each human being responds to music or with it to the various circumstances that life gives him. This research work arises from the need to unite two important pieces, music with and for children and auditory perception. Music and childhood have always been present throughout our professional career, musical pedagogy is nothing other than teaching the infant things through music (melody, son, intonation, accent, etc.). The accumulated experience of the constant practices that we carry out in the educational center of the initial level, gave us the opportunity to verify that through songs children are motivated, learn, internalize knowledge, create life habits and produce movements, develop abilities and skills, that they will use throughout their lives. Music is one of the most important elements in the development of children's auditory sensory abilities, because it allows them to listen and develop behavioral habits. With music, the infant begins to move the hip, clap, dance, sing; Sensory emotions rise and enter an environment of joy and happiness, in essence it can be said that it serves to awaken and develop human faculties.